Student perceptions of an online mathematics curriculum designed for students with learning difficulties - Higgins, Kristina; Crawford, Lindy; Silvestri, Kelly (Social Welfare: Interdisciplinary Approach, 2016)
Paper presents research on the perception of technology use including dimensions of computer self-efficacy, motivation, and independence of use of electronic support tools of students with learning difficulties in the context of an online mathematics curriculum. While all students showed improvement over the course of the program, some students showed more success with technology-based learning than others. Students with stronger academic profiles when beginning the curriculum were more likely to have higher levels of computer self-efficacy. The themes that emerged from the current study reflect motivation and fun, efficiency, and a diversity of learning strategies and support tools available. The themes of motivation and independence are also reflected in electronic support tool use. This indicates that students with different motivating or independently themed factors use the program in different ways by tailoring the electronic support tools to their individual needs.
Keywords: on-line mathematics curriculum; students with learning difficulties; motivation; self-efficiency; independence